The Dragonflies and Damselflies (Insecta: Odonata) of Canada: species list, geographical distribution, status, and conservation ranks - Cannings, Robert A.; Klymko, John; Catling, Paul M.; Savard, Michel; Lemelin, Guy; Jones, Colin D.; Cannings, Sydney G.; Savard, Rémi-Julien (Zootaxa, 2024)
As of August 2023, 220 species in 57 genera and 10 families of damselflies and dragonflies (Insecta: Odonata) are recorded for Canada. Since the publication of the first edition in 2005, 14 species have been added to the list; one, Neurocordulia obsoleta (Say) has been removed because of a misidentification and another, Sympetrum occidentale, has been to synonymy. Conservation ranks are given for species in all 13 provinces and territories. English and French names for all listed species are included. Literature sources are discussed and presented, as is information on species status and the addition and exclusion of species. Sections on taxonomy and variation, subspecies, presumed hybrids, the introduction of exotic species, notable range extensions and observations, and conservation and protection are also provided.